The Role of Social Media in Employee Recruitment: a Systematic Literature Review - Maria Christy Wowor; Deske W. Mandagi; Benny Lule; Shapely S. Ambalao (Jurnal Multidisiplin Madani, 2022)
The objective of this research is to explore the role of social media on employee recruitment. As technology continues to grow, human activities cannot be separated from the use and benefits of technology. Technology also helps companies run their business more efficiently. Social media also plays a crucial role in the recruitment process to find potential candidates. This systematic review paper is written based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) method. The findings show that social media can be used as an effective platform for a faster and more flexible recruitment process. Social media recruitment can also provide advantages for both in terms of cost and time. Furthermore, social media can be a tool for employers to obtain information about candidates' backgrounds